Pengendalian Kecepatan Motor Induksi 3 Fasa menggunakan PLC Omron CP1E dengan Kontrol Proposional - Muhamad Yusuf; Abdul Rohman (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2020)
The industrial automation sector experienced significant developments in the Industrial Revolution 4.0 era. This can be seen with a variety of automation products that have evolved from standalone mode to be integrated with each other. To support the migration from Industry 3.0 to Industry 4.0 communication devices or system updates are needed. The main equipment that must be connected in a control system is the inverter and PLC, because as a driver and control center. Several problems will arise if the PLCs are not connected to each other, such as asynchronous data managed by each PLC, offline data recording and monitoring the performance of each PLC need a relatively long time. This research discusses the method of connectivity between PLCs and inverters for three phase induction motor drives. The inverter used is the LS type SV008iC5 inverter from Industrial LS and PLC that is used is CP1E from Omron Based on research that has been done that the LS type SV008iC5 inverter can interact with PLC type CP1E well. This integration utilizes analog input terminals on the inverter and analog outputs on the PLC. The system has a steady state error below 5% with a maximum speed of 2958 rpm